Human intestinal mucosal mast cells: expanded population in untreated coeliac disease. Issue 3 (March 1983) - Strobel, S; Busuttil, A; Ferguson, A
Abstract : Previous retrospective studies of intestinal mucosal mast cells in coeliac disease have given divergent results, and we have recently reported that inappropriate methodology could account for these discrepancies. In this prospective study, mucosal mast cell counts were performed in Carnoy fixed, peroral jejunal biopsy specimens from patients with coeliac disease, both untreated and treated with a gluten-free diet; and from controls (mainly irritable bowel syndrome). Mean mucosal mast cell count in 27 control subjects was 146/mm2, SD 29. Significantly higher values were obtained in untreated coeliac disease (mean 243, SD 41, p less than 0.001) returning to the normal range in coeliacs treated with a gluten-free diet with normal jejunal biopsy morphology. In seven patients mucosal mast cell counts were performed in multiple jejunal biopsies, and these showed that mucosal mast cell distribution was not patchy. There was no evidence of degranulation of intestinal mucosal mast cells under the conditions of routine biopsy (overnight fast). An increase in mucosal mast cells in untreated coeliac disease may be one explanation for the high number of IgE positive stained cells in the intestinal mucosa that has been reported by some authors.